Choline administration attenuates aspects of the dystrophic pathology in mdx mice. (April 2019) - Alves, Francesca M.; Caldow, Marissa K.; Trieu, Jennifer; Naim, Tim; Montgomery, Magdalene K.; Watt, Matthew J.; Lynch, Gordon S.; Koopman, René
Summary: Background & aims: Dystrophic muscle fibres are fragile and prone to breakage, leading to impaired Ca 2+ homeostasis and excessive inflammation, resulting in muscle wasting and weakness. Choline, an essential water-soluble nutrient, is involved in multiple biological processes, including modulation of inflammation and oxidative stress. We tested the hypothesis that choline supplementation would ameliorate the dystrophic pathology in mdx mice. Methods: Three-week old male mdx mice (n = 40) were fed control purified laboratory chow (CON; n = 20) or a choline-enriched diet (5 g/kg choline; CHL, n = 20) for four weeks. Rotarod performance, grip strength and running (wheel) distance were assessed during treatment. Markers of Ca 2+ -handling, inflammation, oxidative stress and fibrosis were measured in the diaphragm, quadriceps muscle and the liver. Results: Choline-treated mdx mice displayed less macrophage (CD68 -33%, P < 0.05) and collagen infiltration (−34%, P < 0.05) and reduced Tgfβ3 mRNA expression (P < 0.05) in the diaphragm compared to untreated mdx mice. Choline supplementation increased maximal SERCA activity (38%, P < 0.05) and reduced markers of inflammatory ( Tnfα, F4/80 and Cd206 mRNA, P < 0.05) processes compared with untreated mdx mice. In the liver there was a reduction in Acta2 mRNA (P < 0.05) with choline treatment, as well as an improvement in serum ALT levels (P < 0.01). There were no differences between the groups for the whole-body functional analyses. Conclusions: Choline supplementation attenuated the progression of the dystrophic pathology. Although choline did not alter functional performance, the reduction in fibrosis is clinically relevant for increasing the efficacy of therapies for DMD.